1977
DOI: 10.1180/minmag.1977.041.317.10
|View full text |Cite
|
Sign up to set email alerts
|

New data on ktenasite

Abstract: SUMMARY. Ktenasite from Glomsrudkollen zinc mine, Modum, Norway, is menoclinic, space group P21/c.The cell dimensions are a 5'598, b 6.121, c 23'762/~, /5 95.55 ~ The chemical formula is (Cu3.sZnl.5)(SO4)~ (OH)n.6H20 with Z = 2; Pcale 2"96 g/cm 3, Pobs 2"94 g/cm 3. The mineral is biaxial negative with ~ (colourless) 1'574,/5 (bluish green) 1'615, v (light green) 1.628, 2V~ 59 ~ KTENASITE was originally described by Kokkoros (195o) from the Kamariza mine, Laurium, Greece, where it occurs sparingly as blue-gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…The disk was prepared using 200 mg KBr for 1 mg of sample. There are many similarities between the spectrum of the present sample and the dypingite of Raade (1970). A significant difference, however, is …”
Section: J H C a N T E R F O R D Et Almentioning
confidence: 51%
“…The disk was prepared using 200 mg KBr for 1 mg of sample. There are many similarities between the spectrum of the present sample and the dypingite of Raade (1970). A significant difference, however, is …”
Section: J H C a N T E R F O R D Et Almentioning
confidence: 51%
“…This relatively uniform CO2 loss (about 8 ~ by weight) is broken by a dramatic exothermic peak at 510~ followed immediately by a strong endothermic peak and a sudden weight loss of some 15~. Similar exothermic peaks around 500 ~ have been observed during the decarbonation of nesquehonite (Davies and Bubela, 1973), dypingite (Raade, 1970), and hydromagnesite (Sawada et al, 1979) and are interpreted as representing the crystallization of MgCO 3 from a partially decarbonated amorphous intermediate phase. The rapid evolution of heat accompanying this crystallization decomposes the MgCO 3 almost immediately and gives rise to an endothermic reaction and rapid CO2 loss.…”
mentioning
confidence: 58%
“…Subsequently, the mineral was described from Italy and Cornwall by Mellini et al [3]. Olsen and Lewis [6] reported that ktenasite from Creede, Colorado, was richer in zinc than copper [3][4][5][6]. Recently, Ohnishi et al [7] described the first occurrence of ktenasite from Japan and presented EPMA and crystal structure analyses [7].…”
Section: Introductionmentioning
confidence: 95%
“…Ktenasite forms as the result of the oxidation of copper and zinc sulphide minerals. A green platy mineral from the Glomsrudkollen zinc mine, Modum, Norway, was identified as ktenasite by Raade et al [5], and they proposed the chemical formula (Cu,Zn) 5 (SO 4 ) 2 (OH) 6 Á6H 2 O. Subsequently, the mineral was described from Italy and Cornwall by Mellini et al [3].…”
Section: Introductionmentioning
confidence: 99%